1998
DOI: 10.1074/jbc.273.32.20267
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of KIF1C, a New Kinesin-like Protein Involved in Vesicle Transport from the Golgi Apparatus to the Endoplasmic Reticulum

Abstract: Kinesins comprise a large family of microtubule-based motor proteins, of which individual members mediate specific types of motile processes. Using the ezrin domain of the protein-tyrosine phosphatase PTPD1 as a bait in a yeast two-hybrid screen, we identified a new kinesin-like protein, KIF1C. KIF1C represents a member of the Unc104 subfamily of kinesin-like proteins that are involved in the transport of mitochondria or synaptic vesicles in axons. Like its homologues, the 1103-amino acid protein KIF1C consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
113
1
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(121 citation statements)
references
References 60 publications
6
113
1
1
Order By: Relevance
“…Further investigation for other isoforms of KIF1B may help us to understand the function of KIF1B. Kif1C is localized primarily at the Golgi apparatus, and is thought to be involved in transporting Golgi membrane (Dorner et al, 1998). The Kif1C can also form dimers and is associated with proteins of the 14-3-3 family (Dorner et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation for other isoforms of KIF1B may help us to understand the function of KIF1B. Kif1C is localized primarily at the Golgi apparatus, and is thought to be involved in transporting Golgi membrane (Dorner et al, 1998). The Kif1C can also form dimers and is associated with proteins of the 14-3-3 family (Dorner et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Watters et al (17) identified a mutation on a gene named kif1C that is responsible for the different sensitivities of macrophages to LeTx. kif1C encodes a kinesin-like motor protein of the UNC104 subfamily (18). It is clear that proper function of kif1C is required for LeTx resistance, but how this protein is involved in LeTx-elicited changes in macrophages is unknown (17).…”
Section: Anthrax Infections Are Initiated By Endospores Ofmentioning
confidence: 99%
“…An intervening sequence of about 580 residues without apparent homology to known proteins separates the FERM and the PTP domains. PTPD1 regulates signaling induced by Tec family members of membrane receptors (19) and associates with KIF1C, a tyrosine-phosphorylated kinesin-like protein that controls retrograde transport of vesicles from the Golgi apparatus to the endoplasmic reticulum (20). Expression of PTPD1 is significantly elevated in several human cancers (21).…”
mentioning
confidence: 99%